Sion's Quartet Card Breastfeeding (Modified Audio) to Develop Breastfeeding Behavior - Sihombing, Juliana Sion; Andilala, Andilala; Lubis, Nur Azizah; Safriana, Safriana (Jurnal Riset Kesehatan, 2025)
The best nourishment for newborns is breast milk., as it contains all the nutrients they need for healthy growth and development. If given water or other fluids, babies will quickly feel full and will no longer want to breastfeed. Because the images are similar to the subject, using audio-modified breastfeeding quartet cards can help explain problems in the pictures and motivate nursing moms to read and use the proper breastfeeding techniques for their infants.  It is hoped that education using audio-modified quartet cards will change behavior. The goal is to create audio-modified quartet cards and gamification to improve breastfeeding behavior. A control group and an intervention group were included in this study's quasi-experimental pre- and post-test design.  Eight treatments, including teaching materials utilizing a nursing quartet card game and audio-modification for four weeks, were given to a sample of thirty-two respondents who were placed in the intervention group. In the meantime, the control group just got prenatal education classes, questionnaires, and no further treatments. The analysis yielded a p-value of 0.000, indicating that the implementation of audio-modified breastfeeding quartet card gamification by the intervention group was more successful in improving breastfeeding behavior among mothers than the control group, which only received education through prenatal classes. There was a 2.1% increase in behavior in the control group and a 99% increase in the intervention group. Compared to the control group, which only received education through prenatal classes, the intervention group using audio-modified breastfeeding quartet card gamification was more successful in improving breastfeeding behavior in mothers, according to the analysis of unpaired data test with a p-value of 0.000. Sion's Quartet Card Breastfeeding (Modified Audio) To Develop Breastfeeding Behavior.